Coworking spaces in La Paz, Bolivia: Urban effects and potential creation of new opportunities for local economic development - Lucas DuPriest (Institute for Advanced Development Studies (INESAD), 2019)
This paper investigates the location patterns of coworking spaces, the effects of coworking spaces on the local and urban context, and coworking spaces potential opportunities for the creation of local economic development, issues that have been neglected in a Bolivian context by the existing literature. The focus of this paper is on La Paz, Bolivia's political capital and the city in Bolivia which host the largest number of coworking spaces. The paper addresses three main questions: (1) Where are the main locations of coworking spaces in La Paz? (2) to what extent do coworking spaces generate transformative effects on the local respectively the urban scale? (e.g. physical transformations, changes in practices, community building) (3) how do coworking spaces create potential opportunities for local economic development? Desk research demonstrated that location patterns of coworking spaces are concentrated to two main commercial areas of the city, as well as to the main infrastructural and transportation axes. Field research highlighted local and urban effects, such as local community initiatives and micro-urban transformations in both spaces and practices. Lastly, field research assessed coworking spaces role in the socio-economic ecosystem. Three main typologies have been identified: the first type of coworking spaces act as "social entrepreneurship and start-up incubators" with a supportive role and closer ties to social and urban issues, the second type of coworking spaces act as "coffee and cowork incubators" providing cafés with shared workspaces, the third type of coworking spaces act as "real estate business incubators" and are mainly a commercial product responding the demand for flexible office spaces. This paper, therefore, helps to fill the gap in the literature about the location patterns of these new working spaces and their effects at different scales both in terms of spaces and practices, as well as local economic development.
Keywords: D85; L84; O12; O31; 330; coworking spaces; sharing economy; location patterns; urban effects; local economic development; innovation